2016
DOI: 10.1080/17474124.2016.1177788
|View full text |Cite
|
Sign up to set email alerts
|

Child-Pugh, MELD, and ALBI scores for predicting the in-hospital mortality in cirrhotic patients with acute-on-chronic liver failure

Abstract: Child-Pugh, MELD, and ALBI scores might be ineffective in predicting the in-hospital mortality of cirrhosis with ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 18 publications
4
58
1
Order By: Relevance
“…For the assessment of liver function in patients with liver cancer and treated with sorafenib, the resolution of the ALBI score is similar to that of the CTP score for patients with a CTP grade of A, whereas the ALBI grading is superior to the CTP grading for all HCC patients (21). The ALBI score has a predictive efficacy similar to that of the CTP and MELD scores in terms of predicting in-hospital mortality in LC patients with acute upper gastrointestinal bleeding and in ACLF patients with concurrent LC (22,24). In the present study, the ALBI score was compared with the CTP and MELD scores to assess their value in evaluating the liver function of patients with HBV-ACLF, HBV-LC, or HBV-HCC.…”
Section: Discussionmentioning
confidence: 57%
“…For the assessment of liver function in patients with liver cancer and treated with sorafenib, the resolution of the ALBI score is similar to that of the CTP score for patients with a CTP grade of A, whereas the ALBI grading is superior to the CTP grading for all HCC patients (21). The ALBI score has a predictive efficacy similar to that of the CTP and MELD scores in terms of predicting in-hospital mortality in LC patients with acute upper gastrointestinal bleeding and in ACLF patients with concurrent LC (22,24). In the present study, the ALBI score was compared with the CTP and MELD scores to assess their value in evaluating the liver function of patients with HBV-ACLF, HBV-LC, or HBV-HCC.…”
Section: Discussionmentioning
confidence: 57%
“…The ALBI score was developed to assess liver function Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry in patients with hepatocellular carcinoma [18]. However, the ALBI score did not perform satisfactorily in terms of predictive ability in patients with ACLF in a previous study [31]. In the present study, we also analyzed the prognostic value of ALBI score in ACLF and found that it was inferior to that of the ABIC score and that of the MELD score.…”
Section: Discussionmentioning
confidence: 78%
“…) . MELD score was the most commonly used scoring system, which was used in 24 studies (28 cohorts) involving 4663 patients . Followed by CPT score, which was used in 12 studies (16 cohorts) involving 2226 patients .…”
Section: Resultsmentioning
confidence: 99%
“…MELD score was the most commonly used scoring system, which was used in 24 studies (28 cohorts) involving 4663 patients . Followed by CPT score, which was used in 12 studies (16 cohorts) involving 2226 patients . Moreover, eight studies (nine cohorts) involving 1500 patients were included in the analysis of MELD‐Na score .…”
Section: Resultsmentioning
confidence: 99%